2015
DOI: 10.1111/1471-0307.12265
|View full text |Cite
|
Sign up to set email alerts
|

Protein lactosylation in UHT milk during storage measured by Liquid Chromatography–Mass Spectrometry and quantification of furosine

Abstract: The initial stage of the Maillard reaction, protein lactosylation, occurs during heat treatment of milk and continues during subsequent storage. We compared the initial lactosylation as well as the rate of lactosylation of milk proteins during storage in UHT milk subjected to direct or indirect heat treatment using liquid chromatography (LC) coupled with electrospray injection mass spectrometry (ESI-MS). Furosine content was used as an overall marker to allow for a quantitative correlation of lactosylation mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…Siciliano, Mazzeo, Arena, Renzone, and Scaloni (2013) and Siciliano, Rega, Amoresano, and Pucci (2000) reported that the extent of lactosylation accounts for 30% and 70% of the protein in UHT and powdered milk respectively. In a recent study, UHT milk stored up to 6 months at 20 °C showed that the extent and the rate of lactosylation correlated with the number of Lys residues in the different proteins, and a linear correlation with furosine was observed (Rauh et al, 2015); furosine is formed from lactulosyl-lysine by acidic digestion during analysis. Theoretically, lactose can attach to any site of lysine in milk proteins and affect their functional and nutritional properties.…”
Section: Lactosylationmentioning
confidence: 95%
“…Siciliano, Mazzeo, Arena, Renzone, and Scaloni (2013) and Siciliano, Rega, Amoresano, and Pucci (2000) reported that the extent of lactosylation accounts for 30% and 70% of the protein in UHT and powdered milk respectively. In a recent study, UHT milk stored up to 6 months at 20 °C showed that the extent and the rate of lactosylation correlated with the number of Lys residues in the different proteins, and a linear correlation with furosine was observed (Rauh et al, 2015); furosine is formed from lactulosyl-lysine by acidic digestion during analysis. Theoretically, lactose can attach to any site of lysine in milk proteins and affect their functional and nutritional properties.…”
Section: Lactosylationmentioning
confidence: 95%
“…The dilution of the sample with guanidine buffer gave a better resolution of individual proteins compared to dissolution of milk samples in urea buffer as used by Rauh et al (2014), Bonizzi et al (2009), and Visser et al (1991). In the case of whey proteins, higher heat intensity leads to a pre-peak formation due to non-enzymatic glycosylation of whey proteins with lactose as described by Rauh et al (2015). By using this method, we could quantitatively follow the heatinduced aggregation process of individual caseins at heated different temperatures and heat holding times at constant non-fat total solid content of 27% as presented in Fig.…”
Section: Heat-induced Aggregation Of Caseins In Concentrated Skim Milkmentioning
confidence: 99%
“…Molecular weight of proteins in concentrated milk was determined by liquid chromatographyelectrospray ionization time-of-flight mass spectrometry (LC-ESI-TOF-MS) (Agilent Technologies, Santa Clara, CA, USA). Sample preparation was performed according to the protocol, mentioned by Rauh et al, 2015 [73]. Briefly, 200 µL of concentrated milk was treated with 20 µL of 0.5 M DTT, 1 mL of 100 mM trisodium citrate, and 6 M urea at temperature 30 • C for 1 h in a thermostat.…”
Section: Understanding Of Molecular Weight Of Proteins In Concentratementioning
confidence: 99%
“…It may explain by the fact that the electrophoretic mobility of caseins in electrophoresis gel is lower than expected from their molar mass [108]. It may be justified by the fact that phosphorylation [109] and lactosylation of caseins [73] change the migration of casein molecules in electrophoresis gel. However, in SDS-PAGE, several protein aggregates were present, they were absent in mass-spectrum.…”
Section: Molecular Weight Of Different Proteins In Concentrated Milk mentioning
confidence: 99%